2015
DOI: 10.18321/ectj202
|View full text |Cite
|
Sign up to set email alerts
|

New Gas-Phase Catalytic Oxidative Processes for Desulfurization of Diesel Fuel

Abstract: <p>An effective gas-phase oxidative desulfurization (ODS) process was proposed. The process was studied in a laboratory reactor with a proprietary catalyst at 300-400 ºС and ambient pressure with model fuels represented by thiophene, dibenzothiophene (DBT) and 4,6-dimethyldibenzothiophene (DMDBT) dissolved in octane, isooctane or toluene. The reactivity of different sulfur containing molecules in ODS was shown to increase in the sequence: thiophene &lt; DBT &lt; DMDBT. The main sulfur containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…These properties of CNMs, as well as adsorption capacity, the absence of strong acid sites and ability to activate oxygen have drawn attention to their use in the process of selective oxidation of sulfur-containing compounds in fuels [17][18][19][20][21][22][23]. In contrast to oxide supports for which different compositions of active components were studied and favorable compositions were selected [24][25][26][27] the open literature on supported active species on CNMs for oxidative desulfurization is quite limited and their optimal type, content and dispersion is not fully understood so far.…”
Section: Introductionmentioning
confidence: 99%
“…These properties of CNMs, as well as adsorption capacity, the absence of strong acid sites and ability to activate oxygen have drawn attention to their use in the process of selective oxidation of sulfur-containing compounds in fuels [17][18][19][20][21][22][23]. In contrast to oxide supports for which different compositions of active components were studied and favorable compositions were selected [24][25][26][27] the open literature on supported active species on CNMs for oxidative desulfurization is quite limited and their optimal type, content and dispersion is not fully understood so far.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of scientific, technical and patent literature has shown that in order to reduce the content of sulfur and nitrogen oxides in the flue gases from the combustion of coal fuels three main technological methods are used [6,7,8,9,10,11,12,13]:  Reduction of the concentration of sulfur in the original coal coming to power and steam stations;  Reduction of the concentration of sulfur oxides formed during combustion of coal fuel containing sulfur by introducing Sulphur Capture Agents (SCA) in the combustion zone;  Reduction of the concentration of sulfur and nitrogen oxides in flue gases by means of purification of the latter using a number of known methods, most effective of which are methods of sorption and catalytic purification of flue gases.…”
Section: Resultsmentioning
confidence: 99%
“…Economical advisability of this method decreases with stiffening of environmental requirements to the fuel quality, which makes it necessary to develop new approaches to the purification of hydrocarbon feedstock. Oxidative desulfurization (ODS) is among promising alternative methods for the removal of sulfur compounds and has considerable advantages over hydrodesulfurization [5][6][7][8][9][10][11][12][13][14][15]. The ODS process can be performed at lower temperatures and pressures and does not require the use of hydrogen, which is an expensive reagent.…”
Section: Introductionmentioning
confidence: 99%